Improving the Quality of Human Resources in Villages Through Empowerment and Managerial Training Programs - Lubis, Fatimah Malini; Rustiawan, Indra; Siswanto, Agus; Feriyadin, Feriyadin; Setiawan, Roy (Pascasarjana Universitas Mataram, 2024)
This Community Service (PKM) activity aims to improve the quality of human resources in the village through empowerment programs and managerial training that are carried out online. This training focuses on three main aspects: leadership, financial management, and natural resource management. Thirty-five village officials and MSME managers participated in this training through the Zoom application for four sessions. The methods include material presentations, interactive discussions, case simulations, and post-training assistance via WhatsApp and follow-up webinars. The evaluation results showed that 75% of the participants experienced an improvement in managerial skills, especially in decision-making and financial management. In addition, participants' satisfaction with the training reached 85%, with a positive response to how the material was delivered and the relevance of the topic to the needs of the village community. Constraints such as limited internet access are overcome by providing session recordings and modules that can be accessed offline. This program fills the gap from previous research by focusing on economic aspects, leadership capacity building, and sustainable management of natural resources. The online approach in this training has proven to be effective in answering the needs of village communities and bridging geographical and technological limitations, which supports more competitive village development